2014
DOI: 10.1089/jwh.2014.4748
|View full text |Cite
|
Sign up to set email alerts
|

No Association Between Left-Breast Radiation Therapy or Breast Arterial Calcification and Long-Term Cardiac Events in Patients with Breast Cancer

Abstract: In a large single-institutional observational study, no association was found between left-sided breast RT or BAC and subsequent cardiac events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 17 publications
1
4
0
Order By: Relevance
“…Coblentz C et al first observed that radiotherapy promoted TAC in a patient who received radiotherapy for Hodgkin lymphoma in childhood (Coblentz et al, 1986), then other researchers observed that radiotherapy promoted coronary artery and aorta calcification in Hodgkin lymphoma patients with chest radiotherapy (Apter et al, 2006;Miki et al, 2020). However, this study found no correlation between radiotherapy and progression of TAC in breast cancer survivors which is consistent with previous studies (Chang et al, 2013;Soran et al, 2014;Takx et al, 2017). There are some reasons for the different results: Hodgkin lymphoma patients were treated with mediastinal radiotherapy, so the aorta was in the radiotherapy area and received more radiation exposure dose.…”
Section: Discussionsupporting
confidence: 88%
“…Coblentz C et al first observed that radiotherapy promoted TAC in a patient who received radiotherapy for Hodgkin lymphoma in childhood (Coblentz et al, 1986), then other researchers observed that radiotherapy promoted coronary artery and aorta calcification in Hodgkin lymphoma patients with chest radiotherapy (Apter et al, 2006;Miki et al, 2020). However, this study found no correlation between radiotherapy and progression of TAC in breast cancer survivors which is consistent with previous studies (Chang et al, 2013;Soran et al, 2014;Takx et al, 2017). There are some reasons for the different results: Hodgkin lymphoma patients were treated with mediastinal radiotherapy, so the aorta was in the radiotherapy area and received more radiation exposure dose.…”
Section: Discussionsupporting
confidence: 88%
“…They reported no statistically significant relationship between BAC observed on baseline mammography and BAC found on follow-up (post-RT) mammography and later cardiac events. They found that subdividing individuals with a left-sided tumor based on BAC did not predict cardiac events either [15]. We attribute the existence of different results to the diversity of study populations and the complexity of the relationship between the diseases that we think may affect cardiovascular events, let alone the fact that radiotherapy in a patient with breast cancer causes an intense pathophysiological change.…”
mentioning
confidence: 75%
“…There is only one research [15] studied the impact of RT on BAC that we could find in the English liter-…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of the 76 studies, 35 investigated the risk of CVM with respect to RT laterality, 28 studies investigated the risk of CVEs with respect to RT laterality, 7,[10][11][12]16,18,20,22,24,33,[40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] 26 studies investigated the risk of CVM with respect to RT compared with no RT, 5,7,10,14,21,27,29,30,32,38,54,[58][59][60][61][62][63][64][65][66][67][68][69]…”
Section: Resultsmentioning
confidence: 99%